Stability Conditions in the Pure Theory of International Trade: A Rehabilitation of the Marshallian Approach - Amano, Akihiro (Quarterly Journal of Economics, 1968)
I. Introduction, 326. — II. Marshall's stability conditions versus the elasticity criterion, 327. — III. Some related problems, 329. — IV. Temporary equilibrium and its stability, 331. — V. Long-run equilibrium and its stability, 332. — VI. Stability conditions and the elasticities of offer curves, 335. — VII. Concluding remarks, 336.